El concepto de dignidad humana en el derecho indiano : influencias en la historia constitucional argentina - Domínguez Benavides, Alejandro A. (2016)
Fil: Domínguez Benavides, Alejandro A. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina